Analisis Kompetensi Pedagogik Guru PAUD Lulusan Non Sarjana PG PAUD - Anggun Novellyandra; Nabila Sa'idah; Munjayanah Saputri; Rita Kurnia (MAN 4 Kota Pekanbaru, 2025)
The educational background of a teacher strongly shapes the quality of instruction, particularly in early childhood settings where pedagogical decisions must align with children’s developmental needs. This study examines the pedagogical competence of early childhood teachers who graduated from non-Early Childhood Education (non-PAUD) programs an increasingly common condition in many PAUD institutions due to limited availability of qualified teachers. Using a qualitative descriptive approach through observations, interviews, and document analysis, the research focuses on classroom teachers at TK Islam An-Nur Bastari whose academic backgrounds differ from typical PAUD educators. The findings show that the mismatch between educational background and teaching field directly affects teachers’ mastery of developmental theories, lesson planning, and the implementation of play-based learning. Despite this, the study also reveals that pedagogical competence can continue to grow through teaching experience, targeted training, and strong institutional support. These insights highlight the urgency for schools and policymakers to design structured professional development programs, especially mentoring and in-house training tailored for non-PAUD graduates, to ensure quality learning in early childhood education.